Digital transformation with Dataverse for Teams : become a citizen developer and lead the digital transformation wave with Microsoft Teams and Power platform /: become a citizen developer and lead the digital transformation wave with Microsoft Teams and Power platform. (2021) - Nair, Srikumar; Lamanna, Charles
No abstract available